Improving the Professionalism of School Teachers Through The Development of HOTS-Based Learning Models - Widodo, Joko; Permana, Dian Fithra; Oktarina, Nina; Ratnasari, Dwi; Fadlilah, Ashomatul; Maulida, Syakila (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
Community service activities carried out by the community service team for teachers aim to share knowledge and skills about developing a Higher Order Thinking Skill (HOTS)-based learning model. The direct benefit of this community service activity is to increase the knowledge, skills, and experience of school-mobilizing teachers in developing HOTS-based learning models. This community service activity is conducted as training by providing materials and practices for developing HOTS-based learning models. The target audience for this community service activity was 30 teachers in Grobogan Regency. The methods used in this activity were lectures, question-and-answer sessions, discussions, and practice, as well as a Participatory Action Research (PAR) approach that involved teachers in problem identification and training planning, enabling them to actively contribute to their own development and improve the quality of education. The results showed significant improvements, including increased teacher participation in discussion forums, from 40% to 80%, and that 60% of teachers were able to apply new teaching methods after the training. The evaluation included aspects of knowledge, skills, activeness, and attendance, reflecting the positive impact of the training. The impact of this activity includes a significant increase in teachers' knowledge and skills in developing HOTS-based learning models, which, in turn, can support improvements in learning quality in schools and sustainably enhance teacher professionalism.